Diversity and state of conservation of Amazonian waterbodies in the Northeast of Peru - Ortega, Hernán (2006)
The present paper describes the diversity and state of conservation, determinate by a rapid biological inventory, carried out since October 24 to 30 of 2005, at the Amazonian waterbodies from Northeast of Peru, between 680 and 133 m of altitude, among Tarapoto (San Martin) and Yurimaguas (Loreto). Data and samples were collected in 26 stations. Planckton samples were collected with standard net (40 microns), benthos with Surber net and fishes with small mesh seines. Descriptions of each habitat included coordinates (UTM), and limnological characteristics (pH, temperature, conductivity, oxygen). The richness of species of fishes was of 95, dominated by Characiformes and Siluriformes. Richness of species in phytoplankton was of 74, in zooplankton, 22 species and in benthos of 20 species. The conservation state was determined using the Index of Biological Integrity (IBI) for fishes, and EPT index (Ephemeroptera, Plecoptera, and Trichoptera) for the aquatic environments. The results indicate that in the better zones conserved were found in the around of Yurimaguas.